(untitled) (Canadian Dermatology Today, 2021)
Pathological scars, comprising hypertrophic scars and keloids, are both rewarding and challenging to treat in clinical practice. Beyond the cosmetic appearance and the physical reminder of the circumstances of scar formation, patients can also experience itch, pain, or even functional limitations. In many ways, the large number of available treatment options highlight that there is no globally accepted therapeutic ladder for this clinical scenario.